Analisis Sistem dan Kebijakan Israel dalam Pendidikan Agama Islam Arab-Muslim - Aripin, Abdul Malik; Sassi, Komarudin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This article analyzes Israel's education system and policies in the context of Arab-Muslim Islamic education. This research examines how the Israel’s education system and policies influence the development of Islamic education for the Arab-Muslim community and examines the impact of the education system on identity, values and understanding of religion in the Arab-Muslim community in the state of Israel. This study uses a qualitative-descriptive method through analysis of various literary sources and research reports as well as accredited national and international journals, especially those published in the period 2019 to 2024. The results show the need for dialogue and integrative collaboration between various stakeholders in minimizing inequality in policies in the four existing structures and types of schools fairly and wisely. With an inclusive approach, cross-group collaboration, and fair and wise government policies, it is possible that the existence of Arab-Muslim Islamic education has the potential to strengthen social tolerance and the development of Israel's glorious civilization.